Konsep â€œSmart Cityâ€ Dan Tata Kelola Pemerintahan Di Kota Denpasar - I. G. A. AG Dewi Sucitawathi; Wayan Joniarta; Yulyana Dewi (Public Inspiration : Jurnal Administrasi Publik, 2018)
Smart city is a concept created to manage urban systems. The system is integrated into local government information systems, schools, campuses, transportation systems, hospitals, businesses, commerce, power plants, water supply networks, law enforcement, job vacancies and other community services. The concept of smart city itself has actually been applied in several countries such as Turkey, Malta, Stockholm (Sweden), Gujarat (India), Kuching (Malaysia) to several cities in Indonesia such as Bandung, Yogyakarta, Surabaya, Magelang, and Denpasar (Bali). This concept essentially emphasizes on the utilization of information technology (IT) ie internet, social media (medsos) in the life of society. In the local governance (local government) of Denpasar, the concept of 'smart city' is not a new item. Several agencies such as the Office of Communications and Informatics, BPBD Denpasar, Health Office (Diskes), Samsat Office, Immigration Office, Denpasar City Licensing Agency, Kesbangpol Denpasar City and other government agencies have applied this Smart City concept. Benefits with the implementation of online-based system (smart city) is a faster service, easy and efficient.